Refugees in our Own Land: Chronicles from a Palestinian Refugee Camp in Bethlehem by Muna Hamzeh (London and Sterling, VA: Pluto Press, 2001. 166 pages.) (American Journal of Islam and Society, 2003)
Refugees in our Own Land narrates the author’s life between October andDecember 2000, when she was married and living in the West Bank’sDheisheh refugee camp. The book creates a new respect for the refugeesamong whom she lived and gives the reader a glimpse of the incredible difficultiesof their everyday lives.The book is divided into two parts. The first part chronicles Hamzeh’slife during October 4-December 4, 2000: her personal life and that of herfriends in Dheisheh, as well as current political events and how they affectthe life of the refugees in the camp. These almost daily entries were actuallye-mailed to a large number of people while she was still living inDheisheh. The second half of the book is a series of short unrelated storiesand articles, written between 1988 and March 2000, that highlight eventsthat brought her to Dheisheh and explain other events and people in her life.Their order is a bit odd. After the reader gets used to Hamzeh’s life in thecamp, she abruptly ends her entries by describing how she left the camp andthen, just when the reader wants to know what happened next, she startsrelating the events that transpired 2 years ago prior to her journey to theWest Bank. There is no mention of a husband there, and then all of a suddenshe goes from living in the United States to ending up in Dheisheh.How she got there, unfortunately, is never explained. The lack of detailsconcerning such important transitions is quite frustrating. Although shemay have considered them “too personal” to include, it resulted in frustrationon the reader’s part.One success, however, is her exposure of the humanity of people whoso often are dismissed by the world as “refugees.” She mentions their namesand describes their faces and personalities, thereby giving the reader an ...